Bibliotekininkystės ir informacijos mokslų mokymas Jungtinės karalystės universitetuose - Macevičiūtė, Elena (Information & Media, 1996)
The article describes the changes in LIS departments of the United Kingdom universities that took place in the beginning of nineties. The author pays greatest attention to the development of curricula and methods of studies. The variety of programmes and degrees at the LIS schools is great The possibilities to find one, that will suit an individual student best and will ensure his professional career, are great The variety of choices does not mean disintegration of the profession. The core courses and modules offered by different schools include the same main areas of professional activities. The individual studies is the main means to arouse active interest in students. The LIS schools and their staff work hard to achieve this goal and to educate future librarians according to present and future professional standards.